1990
DOI: 10.1007/bf02537157
|View full text |Cite
|
Sign up to set email alerts
|

Tissue phospholipid fatty acid composition in genetically lean (Fa/−) or obese (fa/fa) zucker female rats on the same diet

Abstract: The fatty acid composition of serum total lipids, of phospholipids of various organs (liver, heart, kidney), and of nervous structures (brain, retina, sciatic nerve, myelin, synaptosomes) have been compared in lean (Fa/-) and genetically obese (fa/fa) Zucker female rats. Both received a standard commercial diet including 37% of 18:2n-6 and 5% of n-3 polyunsaturated fatty acids (PUFA), 1.7% of which were in the form of 20:5n-3 and 22:6n-3. In comparison with lean rats, the results for the obese rats pointed out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 43 publications
5
10
0
Order By: Relevance
“…These data are in accordance with recent reports showing decreased elongase activity (increased C16:0 on the costs of C18:0) in muscle of healthy subjects made insulin resistant [7]. In obesity and insulin resistance states, ∆5-desaturase activity was reported to be reduced [4,16,52,54], whereas that of ∆6-desaturase increased [16]. We found little change in ∆5-desaturase and no change in ∆6-desaturase activity indices.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data are in accordance with recent reports showing decreased elongase activity (increased C16:0 on the costs of C18:0) in muscle of healthy subjects made insulin resistant [7]. In obesity and insulin resistance states, ∆5-desaturase activity was reported to be reduced [4,16,52,54], whereas that of ∆6-desaturase increased [16]. We found little change in ∆5-desaturase and no change in ∆6-desaturase activity indices.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports have indicated that elongase activity (18:0/16:0) is reduced in insulin resistance [16,50,52,53]. In this study, we found that elongase activity was decreased in day 5 as assessed by the activity indices found in triglycerides and diglycerides fractions.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Data obtained in genetically obese animals are also equivocal. Contributions of AA to plasma and tissue phospholipid fatty acids were lower in obese Zucker rats (fa/fa) than in lean (fa/-) animals (Guesnet et al, 1990). In contrast, increased conversion of LA to AA was reported in obese mice (Cunnane et al, 1985a).…”
Section: Metabolism Of Essential Fatty Acids In Obese Childrenmentioning
confidence: 82%
“…High D9 and D6 DAs are associated with adiposity and the metabolic syndrome. [14][15][16][17][18] High D5 DA has been associated with normal weight and insulin sensitivity in adults. 15,19 Few studies have assessed the relations of serum lipid fatty acid composition to overweight and CVD risk factors in adolescents and none have included measures of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%